2013
DOI: 10.1007/s11302-013-9364-5
|View full text |Cite|
|
Sign up to set email alerts
|

A1R–A2AR heteromers coupled to Gs and Gi/0 proteins modulate GABA transport into astrocytes

Abstract: Astrocytes play a key role in modulating synaptic transmission by controlling extracellular gamma-aminobutyric acid (GABA) levels via GAT-1 and GAT-3 GABA transporters (GATs). Using primary cultures of rat astrocytes, we show here that a further level of regulation of GABA uptake occurs via modulation of the GATs by the adenosine A 1 (A 1 R) and A 2A (A 2A R) receptors. This regulation occurs through A 1 R-A 2A R heteromers that signal via two different G proteins, G s and G i/0 , and either enhances (A 2A R) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 40 publications
3
115
0
Order By: Relevance
“…On the other hand, adenosine A 2A receptor-mediated GABA uptake by neighboring astrocytes may contribute to neuronal excitation [14], since astroglia dominate the buildup of extrasynaptic GABA that controls the glutamatergic neuronal excitatory drive. In a previous study, Cristovão-Ferreira et al [30] elegantly demonstrated that higher extracellular adenosine levels, such as those occurring during epileptic crisis, favor astrocytic GABA uptake by switching the coupling of A 1 /A 2A heteromers from inhibitory G i to excitatory G s protein proteins signaling. Mixed signal transduction and lateral stabilization of A 1 /A 2A heteromers in the 2:2 conformation has been confirmed recently in heterologous systems [56], but the pathophysiological consequences of altered receptors stoichiometry motivated by epileptic changes is worth to be investigated in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, adenosine A 2A receptor-mediated GABA uptake by neighboring astrocytes may contribute to neuronal excitation [14], since astroglia dominate the buildup of extrasynaptic GABA that controls the glutamatergic neuronal excitatory drive. In a previous study, Cristovão-Ferreira et al [30] elegantly demonstrated that higher extracellular adenosine levels, such as those occurring during epileptic crisis, favor astrocytic GABA uptake by switching the coupling of A 1 /A 2A heteromers from inhibitory G i to excitatory G s protein proteins signaling. Mixed signal transduction and lateral stabilization of A 1 /A 2A heteromers in the 2:2 conformation has been confirmed recently in heterologous systems [56], but the pathophysiological consequences of altered receptors stoichiometry motivated by epileptic changes is worth to be investigated in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes modulate the activity of neuronal networks upon sustained and intense activity, but it has been recently evidenced that astrocytes can also modulate basal synaptic transmission by the release of purines [29]. Interestingly, γ-aminobutyric acid (GABA) uptake in astrocytes has been attributed to the expression of A 1 /A 2A heteromers and to a specific mechanism by which these heteromers signal via inhibitory G i or facilitatory G s depending on the extracellular concentration of adenosine [30]. The astrocytic A 2A receptor also seems to be critical for the modulation of glutamate transport, either by decreasing the uptake [12,13] or increasing the release [11] of this amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BDNF facilitates exocytotic GABA release (B) (present work) and astrocytic GAT-1-mediated uptake of GABA (C) [17]; in both cases, these actions are gated by A 2A R. Direct influences of adenosine over hippocampal GABAergic transmission also occur, and some involving A 2A Rs are depicted in this figure (see [2] for details). Thus, A 2A Rs also directly facilitate GAT-1-mediated GABA transport into nerve endings (A) [52] as well as facilitate GAT-1-and GAT-3-mediated GABA transport into astrocytes (C), these actions being counteracted by an inhibitory action mediated by A 1 R which is heteromerized with A 2A R at the plasma membrane of the astrocytes (C) [53]. Altogether, these A 2A R-dependent actions of BDNF may contribute to increase neuronal excitability without losing temporal fidelity of GABA transmission of GABAergic signaling but also be shortening the time window of GABA action, so increasing, in this way, the temporal fidelity of GABAergic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…[130][131][132][133][134] This same interaction is also seen in cultured cortical astrocytes, where activation of the A 1 R-A 2A R heteromer has a modulatory effect on GABA uptake. 135 In dopaminergic terminals, only A 1 R are expressed, resulting in the tonic inhibition of dopamine release. 132 Postsynaptically, A 1 R and A 2A R are highly expressed in the somatodendritic region of striatal MSNs, and particularly, in the dendritic spines.…”
Section: Striatal Adenosine Neurotransmissionmentioning
confidence: 99%